Application of the ABC curve and its effect on stock accuracy in a clutch kit resale company in the Zona da Mata region of Minas Gerais - Pereira, Leonardo Chahim; Fabbis, Bruno Foureaux; Oliveira, Mario César Fialho de; Oliveira, Patrícia Werneck Silva de; Abreu, Sanderson Rocha de (Brazilian Journal of Production Engineering, 2020)
This study shows the effect of the ABC classification on inventory management, more specifically on stock accuracy. For the development of the present study, a bibliographic review was made about the central themes for the development of the theme and later the practical study was carried out through visits to a clutch KIT reseller company, located in the Zona da Mata Mineira region, with in order to make inventory management viable by applying the ABC Curve, which in turn made it possible to draw up a physical counting plan for the rotating inventory through periods and cycles for each class A, B and C, thus seeking a better accuracy in the company’s stock. It was possible to conclude that the stock management with the application of the ABC curve has a positive effect on the inventory accuracy index, because it helps in structuring the counting plan and in the optimization of decision making, as well as in increasing the accuracy index. Of the stock, where in the company studied the accuracy of the items increased from 64.22% to 97.59%, achieving a better divergence percentage than that established by the company.